2016
DOI: 10.1007/s12275-016-6201-x
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of host and bacterial proteins in sputum from active pulmonary tuberculosis

Abstract: Pulmonary tuberculosis (TB) is caused by Mycobacterium tuberculosis. The protein composition of sputum may reflect the immune status of the lung. This study aimed to evaluate the protein profiles in spontaneous sputum samples from patients with active pulmonary TB. Sputum samples were collected from patients with pulmonary TB and healthy controls. Western blotting was used to analyze the amount of interleukin 10 (IL-10), interferon-gamma (IFN-γ), IL-25, IL-17, perforin-1, urease, albumin, transferrin, lactofer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Jensen et al first identified an association between LTBI and elevated AGP levels (33). TF levels in serum and sputum specimens were significantly higher in active TB patients than in latent TB patients (34). It is difficult to explain the higher levels of SAA and AGP in uninfected cattle.…”
Section: Discussionmentioning
confidence: 96%
“…Jensen et al first identified an association between LTBI and elevated AGP levels (33). TF levels in serum and sputum specimens were significantly higher in active TB patients than in latent TB patients (34). It is difficult to explain the higher levels of SAA and AGP in uninfected cattle.…”
Section: Discussionmentioning
confidence: 96%
“…Upon virus infection, host cells rapidly mount type I IFN responses. Pattern recognition receptors (PRRs) play an important role at the early stage of infection [3,13,[35][36][37][38][39][40][41][42]: MDA5, RIG-I, and toll-like receptors (TLR). MDA5 and RIG-I are known to sense the RNA genome of the invading pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Active pulmonary TB patients particularly the anergic patients, demonstrated markedly elevated IL-10 level, both in serum and bronchoalveolar lavage fluid, suggesting that M. tuberculosis stimulates IL-10 production that in turn disrupts an effective immune response [48,56]. The higher the capacity of IL-10 production is, the greater the risk for developing the disease [57,58]. IL-10 was also found to downregulate M. tuberculosis-induced Th1 responses, thus inhibiting the synthesis of IFN-γ [56].…”
Section: Pulmonary Tbmentioning
confidence: 99%